3D‐Architectured MoS2‐Microflower‐Modified Electrodes toward Electrochemical Determination of Imidacloprid. Issue 10 (10th March 2022) - Haritha, Vijayakumar Sheela; Manuraj, Mohan; Sruthi, Thekke Veedu; Kumar, V. B. Sameer; Kumar, Santhakumari Amma Ravindran Nair Sarath; Shankar, Sarojini Sharath; Rakhi, Raghavan Baby
Abstract: We report the fabrication and analytical performance studies of electrochemical sensors based on hydrothermally grown 3D MoS2 ‐microflower‐modified Glassy Carbon (GCE) and Carbon Paste Electrodes (CPE) for the sensitive detection of the insecticide imidacloprid (IMI). As compared to MoS2 /GCE, the fabricated MoS2 /CPE demonstrates a faster electron transfer and better catalytic ability. MoS2 /CPE sensor delivers its best performance towards the determination of IMI in PBS solution of pH 7.4, owing to its porous nature which can accommodate a higher number of active electrochemical reaction sites. The sensor exhibits a sensitivity value of 2.296 μA μM −1  cm −2 with lower detection and quantification limits of 12±0.24 nM and 40±0.8 nM respectively. The proposed sensor also exhibits linearity in the detection of IMI from 1 to 100 μM. Abstract : 3D architectured MoS2 ‐microflowers were synthesised by a simple hydrothermal method. MoS2‐ modified carbon paste electrodes were fabricated for the sensitive and selective detection of the insecticide Imidacloprid. Voltammetric studies demonstrated the excellent stability and electrocatalytic activity of MoS2 /CPE for IMI reduction. MoS2 ‐microflower‐modified electrodes improve the sensing parameters by facilitating better electron transfer dynamics and providing a huge number of active sites for the electrocatalytic reduction of IMI. The optimized sensor has also shown reproducible results and can be utilized for practical applications.